Development and Performance of Tungsten-Coated Graphitic Foam for Plasma-Facing Components. (18th August 2019) - Youchison, D. L.; Coenen, J. W.; Gray, T. K.; Lumsdaine, A.; Klett, J. W.; Jolly, B.; Gehrig, M.; Brezinsek, S.; Rasinski, M.
Abstract: High-density graphitic foam is an ideal low-Z plasma-facing material for deuterium-deuterium plasma experiments where tritium codeposition is not an issue. However, like all carbon, graphitic foam suffers from a precipitous drop in thermal conductivity at high temperatures, >600°C. To mitigate these problems, functionally graded layers of tungsten can be deposited to a thickness of 2 to 4 mm onto the plasma side of the foam using chemical vapor deposition. The graphitic foam then acts as a high-conductivity heat sink at temperatures below 600°C for the thin high-Z armor coating. The overall component weighs 18 times less than a comparable volume of tungsten and lacks the coefficient of thermal expansion joining issues between the CuCrZr tubing and the tungsten. This paper discusses the coating development and characterization and presents the results of recent plasma exposures in W7-X. It also reports on computational fluid dynamics heat transfer modeling and preparations for high heat flux testing of mock-ups. This hybrid plasma-facing component (PFC) consisting of innovative engineered materials may be a cost-effective, actively cooled solution for the divertors and other PFCs in long-pulse machines like W7-X and WEST.